1996
DOI: 10.1084/jem.184.5.1609
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of T cell receptor peptide-specific CD4 regulatory T cells induces chronic experimental autoimmune encephalomyelitis (EAE).

Abstract: SummaryT cell receptor (TCR)-recognizing regulatory cells, induced after vaccination with self-reactive T cells or TC1K peptides, have been shown to prevent autoimmunity. We have asked whether this regulation is involved in the maintenance of peripheral tolerance to myelin basic protein (MBP) in an autoimmune disease model, experimental autoimmune encephalomyelitis (EAE). Antigen-induced EAE in (SJL X B10.PL)F1 mice is transient in that most animals recover permanently from the disease. Most of the initial enc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
59
0
1

Year Published

1998
1998
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(63 citation statements)
references
References 36 publications
(51 reference statements)
3
59
0
1
Order By: Relevance
“…It is noteworthy that treatment of B10.PL mice with anti-TCR V␤14 mAb results in incomplete recovery and chronic disease, whereas mice treated with anti-V␤3 alone do not show a significant difference in the natural course of EAE (13). These data further suggest the critical role V␤14 ϩ CD4 ϩ Treg play in this model.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…It is noteworthy that treatment of B10.PL mice with anti-TCR V␤14 mAb results in incomplete recovery and chronic disease, whereas mice treated with anti-V␤3 alone do not show a significant difference in the natural course of EAE (13). These data further suggest the critical role V␤14 ϩ CD4 ϩ Treg play in this model.…”
Section: Discussionsupporting
confidence: 53%
“…Furthermore, removal of the V␤14 ϩ T cell repertoire, by anti-V␤14 mAb treatment, results in exacerbation of EAE and is associated with poor recovery (13). Additionally we demonstrated that the adoptive transfer of clones of the V␤14 ϩ Treg in the presence, but not in the absence of CD8 ϩ T cells protected recipients from EAE (9,12).…”
mentioning
confidence: 74%
See 1 more Smart Citation
“…However, the adoptive transfer of MUC1-expanded CD4 ϩ CD25 Ϫ T cells from WT mice to MUC1-Tg mice to raise the level of MUC1-specific T cell help is a proof of principle that we believe can be applied to the clinic where patients would receive transfers of autologous Treg-depleted Th cells that are expanded to large numbers in vitro by stimulation with MUC1. Restoring the balance to the MUC1-specific immune response via the provision of a defined component, such as functional Th cells, may be a more feasible clinical approach to treating malignancies than global depletion of the patients' Tregs, which may be fraught with side effects such as autoimmunity (55)(56)(57)(58)(59)(60).…”
Section: Discussionmentioning
confidence: 99%
“…EAE is suppressed by the activity of Tregs (83)(84)(85)(86), including central Tregs (54,87), via the action of IL-10 (84,86,88). Tregs are induced by CD4 + T cell activation in the presence of TGF-b (86), and their induction is inhibited by IL-6 via trans signaling of soluble IL-6R into T cells causing SMAD7 suppression of TGF-b signaling (89).…”
Section: Role Of Central Regulatory T Cells In Modulating Passivementioning
confidence: 99%